Vaginal sacrospinous ligament fixation versus abdominal sacrocolpopexy for the treatment of vaginal cuff prolapse: A retrospective study (Annals of Medical Research, 2021)
None
Keywords: Pelvic Organ Prolapse; Vaginal Vault Prolapse, Sacrocolpopexy.